Literature Review: Analisis Multimedia untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik - Ananda Putri; Hadi Nasbey; Mohamad Syarif Sumantri (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
PISA results show that Indonesia's science literacy skills are low, so a solution is needed to fix the problem. This study aims to analyze the role of multimedia in improving students' science literacy skills. The method used is by collecting literature review data and then reviewing information from the data that has been collected. Based on the results of this study, it was found that multimedia can improve students' science literacy skills in both the “High” and “Medium” categories, so the use of multimedia in the learning process is considered important to improve students science literacy skills. Text, images, audio, animation, and video contained in multimedia can facilitate students in understanding the material, stimulate students' thinking skills, and create active learning.